Market Engineering in Supply: Ikhtikar of Perspectives Islamic Economics - Damayanti, Arka; Rahman Ambo Mase (Balanca : Jurnal Ekonomi dan Bisnis Islam, 2023)
The market mechanism is guaranteed freedom in Islam. The market is free to determine the means of production and prices, and there should be no interference that results in the destruction of the market balance. But in reality it is difficult to find a market that runs by itself fairly. One of them is the practice of hoarding or what is often referred to as monopolistic practices carried out by producers or sellers so that the availability of basic necessities is getting thinner and scarcer so that they can play prices in the market. Seeing this, this article aims to see whether hoarding practices are a form of market engineering in supply (ikhtikar) and to explain the views of Islamic Economics regarding hoarding practices (monopoly). This article is a library research and uses a qualitative method with a normative approach. The data source used is secondary data derived from books, journals and articles related to the practice of ikhtikar, hoarding, and monopoly as well as how Islamic economics views. The results of this study found that price fluctuations also occur due to fraudulent actions in the market such as hoarding by speculators. The act of hoarding in question is market engineering in supply (ikhtikar). The practice of ikhtikar is strictly prohibited in Islamic Economics because it can disrupt the market mechanism. For this reason, the role of the government as a policy maker is needed to regulate in order to create a fair price.